Promotion, Price and Service Quality for Consumers to Making Purchase Decisions - Saleh, Mohamad Zein; Setiorini, Amanda (Ridwan Institute, 2023)
This literature study of promotions, prices and service quality for consumers in making purchasing decisions was carried out scientifically within the scope of marketing management to develop a research hypothesis whether there is an influence of price on purchasing decisions, an influence of promotions on purchasing decisions and an influence of service quality on purchasing decisions. The method used in this research is a qualitative method through literature review. The results of this study are that promotions can influence consumers to make purchasing decisions, prices influence consumers to make purchasing decisions and service quality can influence consumers to make purchasing decisions.